REPREZENTAREA REALITĂȚII URBANE MOSCOVITE ÎN ROMANUL MAESTRUL ȘI MARGARETA DE MIHAIL BULGAKOV. MAGICUL CU ROL CORECTIV / THE REPREZENTATION OF MOSCOW URBAN REALITY IN THE NOVEL THE MASTER AND MARGARITA ’BY MIHAIL BULGAKOV. THE MAGIC HAVIG A CORECTIVE ROL - Maria Holhoș; Andra Gabriela Holhoș (Incursiuni în imaginar)
The inclusion of the supernatural in Moscow's urban spaces (flats, restaurants, theater halls, the writer’s house, office) is meant to enhance the understanding of reality in its paradoxical nature. The boundary between the real and the unreal blurs due to the integration of opposing categories within the novel, aiming to reveal the complexity of the contemporary world. The inclusion of magic within real spaces, the sudden shifts between reality and imagination, and the metamorphosis of elements from one state to another support the syncretic nature of The Master and Margarita and Mikhail Bulgakov’s approach of maintaining a make-believe tone in recounting events through authorial reluctance. The text’s subtleties allow the author to express both personal and social critiques.